The European Union and Bosnia and Herzegovina: A contribution to the study of politics in plural societies - Simović Vlade; Budimir Željko (Srpska Politička Misao)
The subject of research in this paper is plural societies, the mechanisms of their political-system formation and functioning - concretely comparative research of plurality and consociational organization of the European Union and Bosnia and Herzegovina. The historical heritage of religious, national and ideological conflicts are the building blocks of the plural societies of the European Union and Bosnia and Herzegovina. In addition to the pronounced cultural-political plurality, the joint political-value point and basis of comparison between the European Union and Bosnia and Herzegovina is consociational democracy. The comparative analysis of plural societies and consociational democracy in the European Union and Bosnia and Herzegovina and the conclusions drawn in the paper contribute to the overall knowledge about plural societies and consociational democracy.